Structured Teaching Programme on Knowledge Regarding Management of Obstructed Labor Among Final Year GNM Students - Noorjan K S; Preethi D’Souza (RGUHS Journal of Nursing Sciences)
Background The women of developing countries are at risk of pregnancy-related complications including eclampsia obstructed labour sepsis etc. Obstructed labour is the single most important cause of maternal death and is one of the three leading causes of perinatal mortality with a case fatality rate ranging between 87-100. Objectives To assess the pre-existing knowledge prepare and administer the structured teaching program and to assess the effectiveness of structured teaching program by comparing the pre and post-test knowledge scores regarding the management of obstructed labour.Methods The study was conducted at a selected school of nursing and one group pre-test post-test experimental research design was used for the study. The sample comprised of 60 GNM final year students. The sample was selected by non-probability purposive sampling technique. Data were collected and analysed using descriptive and inferential statistics.Results There was an association between pre-test knowledge levels and educational status of final year GNM students regarding the management of obstructed labour. The remaining variables such as age religion and source of information were found to be non-significant.Conclusion The findings of the study revealed that educating the students was effective in updating the knowledge and skills regarding management of obstructed labour. The study provides valuable insights into its causes consequences and management. The STP helped the subjects to update their knowledge regarding management of obstructed labour